Inflammatory Stratification in Primary Sjögren’s Syndrome Reveals Novel Immune Cell Alterations in Patients’ Minor Salivary Glands - Bharaj, Tamandeep K.; Aqrawi, Lara A.; Fromreide, Siren; Jonsson, Roland; Brun, Johan G.; Appel, Silke; Skarstein, Kathrine (Frontiers in Immunology, 2021)
There is a critical need to deconvolute the heterogeneity displayed by the minor salivary glands of primary Sjögren’s syndrome (pSS) patients. This is challenging primarily because the disease etiology remains unknown. The hypothesis includes that initial events in the disease pathogenesis target the salivary glands, thereby triggering the development of focal infiltrates (≥50 mononuclear cells) and finally germinal center-like structures. However, the proportion of key mononuclear immune cells residing at these sites, in combination with the overall ratio of morphometric tissue atrophy and adipose infiltration within the minor salivary glands (MSG) parenchyma at distinct phases of inflammatory disease establishment and progression have not been quantified in detail. In this cross-sectional study, we intended to address this problem by stratifying 85 patients into mild (S1), moderate (S2), and severe (S3) stages using the Inflammatory severity index. We found that mild (<3%) and marked (≥3%) levels of atrophy were accompanied by the respective levels of adipose infiltration in the non-SS sicca controls (p<0.01), but not in pSS patients. The percentage of adipose infiltration significantly correlated with the age of patients (r=0.458, p<0.0001) and controls (r=0.515, p<0.0001). The CD4+ T helper cell incidence was reduced in the focal infiltrates of the MSG of S2 patients compared to S1 (p<0.01), and in S2 compared to S1 and S3 combined (p<0.05). CD20+ B cells increased from S1 to S3 (p<0.01) and S2 to S3 (p<0.01), meanwhile CD138+ plasma cells diminished in S3 patients compared to both S1 and S2 groups combined (p<0.01). The proportion of patients with anti-Ro/SSA+, anti-La/SSB+, and RF+ increased over the course of inflammatory disease progression and they were significantly more common in the S3 group relative to S1 (p<0.05). On the other hand, S2 patients measured a higher mean salivary flow relative to S1 and S3 patients combined (p<0.05). Our results demonstrate how the proposed Inflammatory severity index stratification revealed pathological cell and tissue-associated aberrations in the salivary component over the course of inflammatory progression, and their correlations to clinical outcomes. This could be directly transferred to the optimization of available diagnostic strategies applied for pSS patients.